Studi Kasus Penerapan Keselamatan Operasi (KO) Pertambangan Perusahaan Tambang Nikel di PT XYZ - Faisal Reza; Ashady Adhe Tri Utama P; Theo Wicaksono (Jurnal Riset Teknik Pertambangan, 2025)
Abstract. Indonesia is a major nickel producer, but this mining activity carries significant Occupational Safety and Health (OHS) risks, as evidenced by 1,642 workplace accidents and 224 worker deaths in the last ten years, according to Minerba One Data Indonesia (2024) data. One of the key elements of Operational Safety (OHS) is the management of Facilities, Infrastructure, Installations, and Equipment (SPIP). This study aims to analyze risks and formulate an OHS mitigation strategy in the management of SPIP at the nickel mining company PT XYZ, using a quantitative descriptive approach, to mitigate risks in accordance with the Decree of the Minister of Energy and Mineral Resources Number 1827 of 2018. The study results show that although the majority of SPIP (a total of 1,040 units) are in good condition, there is a crucial weakness: the commissioning period of most units has expired (December 2024–January 2025). In addition.A significant competency gap in engineering personnel was found (for example, 59 people in other fields) and high risks (High) in operational aspects such as mine road standards, mine walls, and sediment ponds. Accident data also highlighted dump trucks as the most dominant equipment involved in incidents (44%). Strategic recommendations include extending immediate commissioning, increasing maintenance schedules, routine training of engineering personnel, and adopting digital technology for SPIP monitoring. These implementations are important to support regulatory compliance, improve the safety, efficiency, and sustainability of mining operations. Abstrak. Indonesia adalah produsen nikel utama, namun aktivitas pertambangan ini membawa risiko Keselamatan dan Kesehatan Kerja (K3) signifikan, terbukti dari 1.642 kejadian kecelakaan kerja dan 224 pekerja meninggal dunia dalam sepuluh tahun terakhir, menurut data Minerba One Data Indonesia (2024). Salah satu elemen kunci Keselamatan Operasi (KO) adalah pengelolaan Sarana, Prasarana, Instalasi, dan Peralatan (SPIP). Penelitian ini bertujuan menganalisis risiko dan merumuskan strategi mitigasi KO pada pengelolaan SPIP di perusahaan tambang nikel PT XYZ, dengan pendekatan deskriptif kuantitatif, untuk memitigasi risiko sesuai Keputusan Menteri ESDM Nomor 1827 Tahun 2018. Hasil studi menunjukkan bahwa meskipun mayoritas SPIP (total 1.040 unit) berada dalam kondisi layak, terdapat kelemahan krusial: masa berlaku komisioning sebagian besar unit telah habis (Desember 2024–Januari 2025). Selain itu, ditemukan gap kompetensi tenaga teknik yang signifikan (misalnya, 59 orang di bidang lain-lain) dan risiko tinggi (High) pada aspek operasional seperti standar jalan tambang, dinding tambang, dan sediment pond. Data kecelakaan juga menyoroti dump truck sebagai alat yang paling dominan terlibat dalam insiden (44%.Rekomendasi strategis mencakup perpanjangan komisioning segera, peningkatan jadwal pemeliharaan, pelatihan rutin tenaga teknik, dan adopsi teknologi digital untuk pemantauan SPIP. Implementasi ini penting untuk mendukung kepatuhan regulasi, meningkatkan keamanan, efisiensi, dan keberlanjutan operasi pertambangan.